Improvement of the Layer Adhesion of Composite Cardiac Patches. Issue 9 (11th November 2019) - Ruther, Florian; Zimmermann, Anne; Engel, Felix B.; Boccaccini, Aldo R.
Abstract : The major purpose of cardiac patches is to deliver healthy cells to infarcted tissues. Such cardiac patches must fulfill specific mechanical as well as chemical requirements. Herein, bi‐component cardiac patches are investigated with regard to their layer adhesion. Combinations of salt‐leached porous poly (glycerol sebacate) (PGS) films with a layer of electrospun‐gelatin fibers are produced. Gelatin fibers are fabricated by solution electrospinning using 20 wt% gelatin in 98 v% formic acid. Fibers are attached to PGS films either via direct electrospinning on top of the film or via combining as spun fiber mats with PGS using gelatin as glue. Scanning electron microscopy (SEM) images show that fiber mats adapt to the rough surface of the porous PGS film. In contrast, fibers spun directly onto films show poor adhesion and only a few fibers are attached to the PGS substrate. Fourier transform infrared (FTIR) analysis, contact‐angle measurements, and pull‐off adhesion tests of the bi‐component patches confirm these results. Modified pull‐off adhesion tests of the two layers show that combining as spun gelatin fiber mats with porous PGS substrates by gluing leads to excellent material adhesion before and after incubation for up to 14 days. Abstract : Bilayered cardiac patches are investigated with regard to the adhesion between layers and mechanical stability. Porous poly(glycerol sebacate) (PGS) membranes are combined with electrospun gelatin fibers either via direct electrospinning on top of PGS or by using gelatin as glue. Different characterization techniques confirmed the excellent material adhesion before and after incubation for up to 14 days in phosphate‐buffered saline (PBS).